Kajian terhadap kepentingan komponen teknologi (Technoware) di kalangan PKS Bumiputera di Negeri Kedah menggunakan pendekatan Proses Analisis Hirarki (AHP) - Yaakob, Mazri; Radzuan, Kamaruddin; Osman, Nor Hasni; Rahim, M.K.I.A. (Penerbit UTM Press, 2015)
This study is discussing about the usage and ownership of technology by SMEs.Technoware is one of the four components of technology that has been highlighted by the researchers.The other components are Humanware, Infoware and Orgaware. Technoware has its elements of its own. A total of 51 Bumiputera SMEs in manufacturing industry in the state of Kedah were selected to be the respondent and the data they obtained through directory PKNK, FMM and SME Corp Malaysia. Data analysis was made using the approach Analytic Hierarchy Process (AHP).Results show Technoware contributes and be a greater emphasis on SMEs.